The Fishing Activity on North Seasons in The Village of Batu Limau Ungar Subdistrict Karimun Regency Riau Island Province of Indonesia - Andika Irwan; Firman Nugroho; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in May 2016 in the village of Batu Limau Ungar District of Karimun Regency of Riau Island province. The object of the studies is to decide the activity of the fishing when North Season and find out the causes of the fisherman who fishing and do not to fishing during the Northen Season. The method that used in this research is case study method with qualitative approach. The informant is this research is 8 owner fishermen who used Gumbang and 4 fishermen who used fishing net. That the amount of the imformants in this research were 12 persons.Based on the research the fishing activity in Batu Limau Village when North Season are influenced by the condition of fishing area and type of fishing gear used, then reducing the leGTh time of fishing. Activities that can be carried out by fishermen are making arrests and find another job when you're not looking for fish. The cause of fisherman fishing at the time of the North Season is conditions are decreased, load and dependents they have, and the change of the spread of fish an opportunity to get the catch more fish. While the fishermen who not fishing is the limitation fishing tools, the condition of the fleet to catch inadequate and dangerous the change of the catchment area.Keywords: Activities, Fishermen, North season, Batu Limau, Karimun